Komunikasi Politik Anggota Legislatif Perempuan di Kota Majalengka - Nurannafi FSM (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2018)
Political communication is considered as a process of conveying political messages from the political elite to the community. In return, the conveyed political message obtains the expected response such as the process of political decision-making in a democratic, transparent, and accountable. Political communication of women legislators in the policy has distinctive characteristics for each member. This is due to the cultural factors and party policy systems that are very influential on the carrier of women legislators. This study aims to determine the political communication of female legislators in the budget preparation policy of Community Empowerment, Women and Family Planning Board in Assembly at Majalengka Regency . The unit of analysis carried out in this research includes the communication of undertaken process related to communicators, the contents of messages that were conveyed, the media used, the communication objectives, as well as the preparation and formulation of strategies in the budgeting policy of the Community Empowerment, Women and Family Planning Board conducted by legislators of Majalengka Regency.